2014
DOI: 10.3390/nu6010342
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Intakes from Food and Supplements in Australian Adolescents

Abstract: Objective: Low micronutrient intakes in adolescents are frequently reported. We assessed micronutrient intakes in adolescents to determine whether supplement use optimises intakes. Methods: Dietary intake was assessed using a food frequency questionnaire in 17 year old participating in the Western Australian Pregnancy Cohort (Raine) Study (n = 991). We calculated median daily micronutrient intakes in supplement users and non-users (from food sources only and from food and supplements), along with the percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 33 publications
5
21
1
3
Order By: Relevance
“…Our findings show that all adolescents have lower calcium and vitamin D intake than RDA. This result is similar to several studies conducted in Australia and the United States [15], [16]. In contrast with our study, Larson and her colleagues stated that calcium intake at 15 years old was significantly higher than calcium intake at 20 years old [30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings show that all adolescents have lower calcium and vitamin D intake than RDA. This result is similar to several studies conducted in Australia and the United States [15], [16]. In contrast with our study, Larson and her colleagues stated that calcium intake at 15 years old was significantly higher than calcium intake at 20 years old [30].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast with these studies, it has shown that the American adults were given 2x400 mg calcium/day for 16 weeks did not reduce the risk of DM [14]. In adolescents life, several studies have revealed that micromineral intake including calcium and vitamin D is lower than the recommended micromineral intake [15], [16]. Adolescents who have irregularly lunch meal will consume more fast foods and less healthy foods that consist of low fiber and micronutrients [17].…”
Section: Introductionmentioning
confidence: 99%
“…Преваленција неадекватног уноса магнезијума код испитиваних ученика (68,6-94,4%), слична је преваленцији утврђеној код адолесцената узраста 14-18 година на Кипру (85-89,9%) 17 , САД (78-94,5%) 21,22 и Бразилу (81,8-99,3%) 18 . Просечан дневни унос магнезијума код адолесцената узраста 17 година у Аустралији био је 309,1 mg код испитаника мушког пола, са преваленцијом неадекватног уноса од 57,3% и 248,1 mg код испитаника женског пола, са преваленцијом од 68,4% 23 . Ове вредности просечног уноса магнезијума сличне су онима код испитаника средње школе (301,03 mg за мушки пол и 265,53 mg за женски пол).…”
Section: материјал и методеunclassified
“…ке преваленције неадекватног уноса гвожђа, због неадекватних образаца исхране и мањег уноса меса, пре свега код девојчица узраста 11-18 година у Данској, Француској, Пољској, Холандији и Уједињеном Краљевству (55-94%), а у случају фолата због мањег уноса њима богатих намирница у Шпанији (63%), Пакистану (85,4%) и Аустралији (93,5%), што у оба случаја може представљати фактор ризика за развој анемије 23,25,26 .…”
unclassified
See 1 more Smart Citation